Respuesta :

Answer:

Step-by-step explanation:

The given quadratic equation is expressed as

x² - 6x - 40 = 0

The equation is already in the standard form of ax² + bx + c

The general formula for solving quadratic equations is expressed as

x = [- b ± √(b² - 4ac)]/2a

From the equation given,

a = 1

b = - 6

c = - 40

Therefore,

x = [- - 6 ± √(- 6² - 4 × 1 × - 40)]/2 × 1

x = [- 6 ± √(36 - - 160)]/2

x = [- 6 ± √196]/2

x = (- 6 + 14)/2 or x = (- 6 - 14)/2

x = 8/2 or x = - 20/2

x = 4 or x = - 10

ACCESS MORE